Marco jurídico de la gestión ambiental para PyMEs Agrícolas: Contexto Caribe Colombiano (2023)
The objective of this work is to identify the legal framework of environmental management for agricultural SMEs in the district of Santa Marta in the Colombian Caribbean. The target population is 97 SMEs, in each one a questionnaire was applied to the person responsible for carrying out the activities related to the production process. The collection was made based on the technique of the survey. This questionnaire is composed of a total of six items, structured with closed multiple-choice questions, with five Likert scale response alternatives. A score was obtained that defines the closing of the dimensions in 3.90, which means according to the classification of the scale a medium agreement, evidencing the sample of weaknesses in the environmental policies and regulations, that is to say that there is a lack of knowledge of what they must comply with and what has been established by the Colombian state, which has generated inconveniences in its social development. © 2019.